Cholinesterase and Liver Enzymes in Patients with Organophosphate Poisoning (Journal of Nobel Medical College, 2019)
Background: Organ phosphorus compounds are one of the most common causes of insecticide poisoning worldwide leading to high degree of morbidity and mortality especially in the developing countries like Nepal. The liver is the main organ that metabolizes various compounds including toxins, chemicals and drugs and eventually excretes from the body. Few studies have been done in Nepal to see the level of liver enzymes among the organ phosphorus compounds poisoning. This may helps in early diagnosis of acute hepatic failure and reduces OP poisoning related death.Materials and Methods: Retrospective chart review study was done with organophosphate poisoning attending Emergency Department followed by admission to Medicine ward or ICU of Dhulikhel Hospital from April 2014 to September 2017. And, laboratory data was extracted from laboratory software, MIDAS version 3.2. After collection of data, statistical analysis was carried out using Statistical Package for Social Sciences (SPSS) version 21 software.Results: Majority of the patients with organophosphate poisoning were female with 64.8% and the majority (31.5%) of patient were of age group in the age group 16-25. Plasma cholinesterase level was found to be significantly decreased in the patients with organophosphate poisoning. Random blood sugar was significantly found to be raised in this study (125.77±52.3), p-value0.04. Among all liver enzymes, there is a significant negative correlation of Cholinesterase with AST (r = -0.35; p-value